E-057 Endovascular treatment of posterior cerebral artery aneurysms with the pipeline embolization device. (23rd July 2017) - Wallace,; Grossberg, J; Almandoz, J Delgado; Kamran, M; Roy, A; Kayan, Y; Austin, M; Howard, B; Moran, C; Cawley, M; Cross, D; Dion, J; et al.
Abstract : Background and Purpose: The Pipeline Embolization Device (PED; Covidien, Irvine, CA) is being increasingly utilized for off-label indications, but has not been widely utilized to treat posterior cerebral artery (PCA) aneurysms. Potential concerns regarding placement of the PED in the PCA include the relatively small parent vessel diameter and coverage of major branch vessels and P1 thalamic perforators. Herein, we report our experience using the PED for the treatment of PCA aneurysms. Materials and Methods: Institutional review board approval was obtained to retrospectively review the neurointerventional databases of three high-volume neurovascular centers for PCA aneurysms treated with the PED between January 2012 and January 2016. Demographic information, clinical history, and outcomes were collected from electronic medical records. Procedural details and periprocedural complications were collected from operative reports. Preoperative digital subtraction angiography (DSA) was reviewed to determine aneurysm characteristics and anatomy of surrounding branch vessels. Follow up MR and DSA were reviewed for aneurysm occlusion, stenosis within the PED, and the status of branch vessels covered by the PED. Results: The study included 10 PCA aneurysms in 9 patients (3 men, 6 women) with a mean age of 56 years (range, 18–74 years). There were 6 saccular aneurysms with a mean aneurysm size of 12.3 mm (range, 7–16 mm), and 4 fusiform aneurysms with mean size of 6.2 mm (range, 3.9–11.0 mm) and mean length of 18.8 mm (range, 5–45 mm). Eight aneurysms were treated with a single PED, and two aneurysms were treated with two PEDs. The PEDs ranged from 2.5–4.25 mm in diameter and 12–35 mm in length. Six of 10 PEDs were deployed entirely within the PCA. In two patients, the PED extended from the PCA into the basilar artery, covering the contralateral PCA and both superior cerebellar arteries. There were no deaths. There were two intraprocedural thromboembolic events (20%; 2/10), one of which resulted in symptomatic infarction (10%; 1/10), and one case of delayed PED thrombosis (10%; 1/10). Angiographic follow up was obtained for 9 of 10 aneurysms, including MRA for two patients, DSA for five patients, and DSA at 6 months and CTA at 24 months for one patient. The mean duration of angiographic follow up was 16.7 months (range, 2–33 months). Excluding the case of delayed parent vessel thrombosis, complete aneurysm occlusion was achieved in 75% (6/8) of cases at longest follow up during the study period. There were no instances of in-stent stenosis. All major branch vessels covered by a PED were patent at last angiographic follow. Conclusions: PED embolization may be a viable treatment option for select PCA aneurysms that may be considered under appropriate clinical circumstances. Disclosures: A. Wallace: None. J. Grossberg: None. J. Delgado Almandoz: None. M. Kamran: None. A. Roy: None. Y. Kayan: None. M. Austin: None. B. Howard: None. C. Moran: 2; C; Medtronic Neurovascular, Microvention. M. Cawley: None. D. Cross: None. J. Dion: None. A. Kansagra: None. J. Osbun: None.